1994
DOI: 10.3146/i0095-3679-21-2-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Virginia-type Peanut Cultivars for Resistance to Southern Corn Rootworm1

Abstract: Southern corn rootworm (SCRW) (Diabmtica undecirnpundata howafdi Barber) is the most damaging soil insect to peanut (Arachis hypogaea L.) in the Virginia-North Carolina production area. New dM and advanced breeding lines have not been evaluated for resistance to SCRW. The objective of this 3-yr study was to evaluate three new cultivars (NC-V 11, VA-C 92R, and AgraTech VC-1) and an advanced breeding line (VA 861101) for resistance to SCRW. NC 6 and NC 9 were used as resistant and susceptible checks, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…NC 7 was included in the bioassays to serve as the susceptible control because it is a commercially available cultivar with no documented resistance to SCR. NC 6 was included as the resistant control because it was released as a resistant cultivar and has been used as the resistant control in previous studies (Coffelt and Herbert, 1994;Petka et al, 1997). The five breeding lines were tested because earlier field evaluations indicated some level of resistance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NC 7 was included in the bioassays to serve as the susceptible control because it is a commercially available cultivar with no documented resistance to SCR. NC 6 was included as the resistant control because it was released as a resistant cultivar and has been used as the resistant control in previous studies (Coffelt and Herbert, 1994;Petka et al, 1997). The five breeding lines were tested because earlier field evaluations indicated some level of resistance.…”
Section: Methodsmentioning
confidence: 99%
“…Resistant peanut cultivars have the potential to reduce or eliminate the need for pesticides currently used to manage SCR infestations (Campbell and Wynne, 1985). Traditionally, peanuts have been evaluated for resistance through field tests (Fronk, 1950;Bousch and Alexander, 1965;Alexander and Smith, 1966;Chalfant and Mitchell, 1970;Coffelt and Herbert, 1994). Although field tests are considered the most reliable measure of resistance, variable SCR populations and environmental factors require field tests to be repeated a minimum of 3 yr for trends in resistance to be established.…”
mentioning
confidence: 99%
“…For example, cv. VA 93B, the fastest maturing commercially available virginia-type pea nut (Coffelt and Herbert, 1994), was observed with fewer pods punctured by rootworm compared to slower maturing lines in fields where several cultivars are grown (Herbert, unpub. data).…”
Section: Methodsmentioning
confidence: 99%
“…While rootworm injury rarely exceeds 25% in southeast Virginia (Miller, 1943), there are extreme cases with 30% (Herbert et al, 1998) to over 60% (Bousch et al, 1963) damaged pods. Coffelt and Herbert (1994) reported that insecticide treatments significantly reduced the amount of damage from rootworm and increased yield, value, and total sound mature kernels. These treatments are usually made at pegging (Phipps et al, 1992) or the R2 growth stage (Boote, 1982).…”
mentioning
confidence: 99%